Analysis of Superior Economic Potential in South Tangerang City with Banten Province Comparator Using Location Quotient, Dynamic Location Quotient, and Shift Share Analysis Methods - Khairullah, Muhammad Qabus Abid; Widiastuti, Rastika; Putri, Cindy Adria Ananda; Anggrahita, Hayuning (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2026)
Gross Regional Domestic Product (GRDP) is a key indicator for understanding regional economic structure and dynamics. Differences in sectoral contributions reflect levels of specialization, competitiveness, and growth potential, making comparative and dynamic sectoral analyses essential for regional development planning. This study aims to identify leading, supporting, potential, and lagging economic sectors using Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share Analysis by comparing the economic performance of South Tangerang City with Banten Province. The analysis is based on GRDP at constant prices by industrial sector for the period 2019-2023. LQ is applied to identify sectoral comparative advantages, DLQ to assess relative growth dynamics, and Shift Share Analysis to evaluate local competitiveness. The results show that South Tangerang City’s economy is predominantly driven by the tertiary sector. Business Services emerge as the only leading sector (LQ > 1 and DLQ > 1), indicating strong structural advantages and favorable growth prospects. Information and Communication, Trade, Construction, Real Estate, Education, and Health Services are classified as base but non-prospective sectors, reflecting a mature development phase. Meanwhile, Public Administration and Electricity and Gas Supply are identified as non-base yet prospective sectors.